Alternative RNA Splicing Expands the Developmental Plasticity of Flowering Transition - Park, Young-Joon; Lee, June-Hee; Kim, Jae Young; Park, Chung-Mo (Frontiers in Plant Science, 2019)
Precise control of the developmental phase transitions, which ranges from seed germination to flowering induction and senescence, is essential for propagation and reproductive success in plants. Flowering induction represents the vegetative-to-reproductive phase transition. An extensive array of genes controlling the flowering transition has been identified, and signaling pathways that incorporate endogenous and environmental cues into the developmental phase transition have been explored in various plant species. Notably, recent accumulating evidence indicate that multiple transcripts are often produced from many of the flowering time genes via alternative RNA splicing, which is known to diversify the transcriptomes and proteasomes in eukaryotes. It is particularly interesting that some alternatively spliced protein isoforms, including CO and FT2 function differentially from or even act as competitive inhibitors of the corresponding functional proteins by forming nonfunctional heterodimers. The alternative splicing events of the flowering time genes are modulated by developmental and environmental signals. It is thus necessary to elucidate molecular schemes controlling alternative splicing and functional characterization of splice protein variants for understanding how genetic diversity and developmental plasticity of the flowering transition are achieved in optimizing the time of flowering under changing climates. In this review, we present current knowledge on the alternative splicing-driven control of flowering time. In addition, we discuss physiological and biochemical importance of the alternative splicing events that occur during the flowering transition as a molecular means of enhancing plant adaptation capabilities.